Human Skeletal Muscle Mitochondrial Adaptations Following Resistance Exercise Training - Parry, Hailey A.; Roberts, Michael D.; Kavazis, Andreas N. (International Journal of Sports Medicine, 2020)
It is universally accepted that resistance training promotes increases in muscle strength and hypertrophy in younger and older populations. Although less investigated, studies largely suggest resistance training results in lower skeletal muscle mitochondrial volume; a phenomenon which has been described as a “dilution of the mitochondrial volume” via resistance training. While this phenomenon is poorly understood, it is likely a result of muscle fiber hypertrophy outpacing mitochondrial biogenesis. Critically, there is no evidence to suggest resistance training promotes a net loss in mitochondria. Further, given the numerous reports suggesting resistance training does not decrease and may even increase VO2max in previously untrained individuals, it is plausible certain aspects of mitochondrial function may be enhanced with resistance training, and this area warrants further research consideration. Finally, there are emerging data suggesting resistance training may affect mitochondrial dynamics. The current review will provide an in-depth discussion of these topics and posit future research directions which can further our understanding of how resistance training may affect skeletal muscle mitochondrial physiology.
Keywords: mitochondrial physiology; hypertrophy; myofiber; citrate synthase